Incontro Fuori Luogo. Interview with Kath Browne - Urciuoli, Carmine (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
Kath Browne is Professor of Geographies of Sexualities and Genders at University College Dublin. Her research interests lie in the social geographies of difference with a specific focus on sexualities and genders. She seeks to use research to make positive social changes, in part through creating collaborative and cross-sector networks and outputs. Her studies opened new questions about the intersections of geographies, sexualities, sex and gender.